Familial and Clinical Correlates in Depressed Adolescents with Borderline Personality Disorder Traits - Guilé, Jean-Marc; Huynh, Christophe; Breton, Jean-Jacques; De La Rivière, Sébastien Garny; Berthiaume, Claude; St-Georges, Marie; Labelle, Réal (Frontiers in Pediatrics, 2016)
Introduction Chart review is a low-cost, but highly informative, method to describe symptoms, treatment, and risk factors associated with borderline personality disorder (BPD) and to adapt screening and intervention to clinical reality. Previous chart review studies report more aggressiveness/anger and psychotic features in youths with BPD. They show that adverse family environment and parental psychopathology constitute important factors for BPD pathology. Objectives To examine clinical characteristics of depressed BPD adolescents (12–17 years old) outpatients according to gender and to explore variables which are associated with BPD traits. Methods A retrospective chart review using the child and adolescent version of the retrospective diagnostic instrument for borderlines was conducted on 30 depressed adolescents with BPD traits and 28 depressed patients without BPD traits. Participants who reached the retrospective diagnostic instrument for borderlines threshold for BPD were included in the BPD traits group. Comparison analyses were performed using Pearson’s Chi-square test. Associated factors were determined using regression analyses. Results BPD traits participants were characterized by higher family problems (parental psychopathology, parent disagreement/argument, and parent–child relational problem), more aggressive symptoms, and higher rates of family intervention and hospitalization. A number of familial factors (parental history of delinquency, substance use, personality disorders, having siblings, or parental disagreement/argument in boys) were associated with BPD traits. Attention seeking and problematic functioning (does not adapt well to group activities) were also associated with BPD traits. Discussion Our study stresses the need to assess BPD traits in adolescent psychiatric evaluation, especially in the presence of aggressive behaviors, family problems and attention seeking. Our results also highlight the importance of exploring family characteristics intervention in adolescents with BPD traits.